2017
DOI: 10.1259/bjr.20160403
|View full text |Cite
|
Sign up to set email alerts
|

DPC4 gene expression in primary pancreatic ductal adenocarcinoma: relationship with CT characteristics

Abstract: Objective: To investigate the relationship between CT imaging findings and DPC4 gene expression and to determine the prognostic value of DPC4 gene expression to predict overall survival in patients with pancreatic ductal adenocarcinoma. Methods: Between January and December 2011, we retrospectively analyzed 163 pancreatic ductal adenocarcinomas in 163 patients who had undergone surgical resection (mean age 5 61.8 years; range 5 35-81 years). We divided the study patients into two groups according to DPC4 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Six of these parameters supported the hypothesis. Regarding the qualitative analysis, we found that tumors with ill-defined margins were significantly more common among metastatic patients: this finding is in line with the study by Choi et al, which observed that PDACs with well-defined margins were significantly associated with DPC4 expression, a tumor-suppressor gene known to have a pivotal role in widespread metastases [ 15 ]. Moreover, hypodense tumors on portal-phase images were significantly more frequent among patients with metastatic spread; this finding was corroborated by the analysis of the density values, that showed lower attenuation values in metastatic patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Six of these parameters supported the hypothesis. Regarding the qualitative analysis, we found that tumors with ill-defined margins were significantly more common among metastatic patients: this finding is in line with the study by Choi et al, which observed that PDACs with well-defined margins were significantly associated with DPC4 expression, a tumor-suppressor gene known to have a pivotal role in widespread metastases [ 15 ]. Moreover, hypodense tumors on portal-phase images were significantly more frequent among patients with metastatic spread; this finding was corroborated by the analysis of the density values, that showed lower attenuation values in metastatic patients.…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports have shown that a radiomic approach to PDAC may show promising results [ 12 , 13 , 14 ], but the application of such analysis to clinical practice is still very limited, due to its complexity. However, a simplified approach to radiomics may be feasible: for example, Choi et al [ 15 ] reported a correlation between non-complex features, as tumor margins, and DPC4 expression in PDAC patients. Since metastases are the most relevant negative prognostic factor in pancreatic ductal adenocarcinoma, the availability of biomarkers that could identify patients that will likely develop metastases would be useful to stratify patients’ prognosis and to optimize their therapeutic management [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this last point, the selection of few, simple (that means, easily to be interpreted) features is a relevant approach [ 17 , 18 ] when compared to more complex radiomic signatures relying on several features of doubtful clinical significance, frequently weakening validation for clinical use [ 19 , 20 ]. As an example of interpretable features in the setting of pancreatic adenocarcinoma, Choi and colleagues, for instance, reported a correlation between non-complex shape features like irregular margins and DPC4 expression [ 21 ].…”
Section: Introductionmentioning
confidence: 99%